Impact of delay in early swallow screening on pneumonia, length of stay in hospital, disability and mortality in acute stroke patients. Issue 11 (November 2018) - Han, Thang; Lean, Michael; Fluck, David; Affley, Brendan; Gulli, Giosue; Patel, Tasmin; Barrett, Christopher; Kakar, Puneet; Sharma, Sapna; Sharma, Pankaj
Abstract Background/Objectives Early swallow screening, within 4 h of admission, is required for all acute stroke patients to commence nutritional support, as recommended. We evaluated the impact of delay in early swallow screening on outcomes in patients admitted with acute stroke. Subjects/Methods Prospective cohort study of 1656 men (mean ± SD age = 73.1y ± 13.2) and 1653 women (79.3y ± 13.0) admitted with stroke to hyperacute stroke units (HASUs) in Surrey. Logistic regression was used to assess the risk (adjusted for age, stroke severity and co-morbidities) of delay in swallow screening on pneumonia, length of stay (LOS) > 3 weeks in HASU or hospital, moderately severe to severe disability on discharge (modified Rankin scale score = 4–5) and mortality during admission. Results Compared with those who received swallow screening within 4 h of admission, a delay between 4 and 72 h was associated with greater risks of pneumonia: OR = 1.4 (95%CI:1.1–1.9, P = 0.022), moderately severe to severe disability on discharge: OR = 1.4 (1.1–1.7, P = 0.007) and a delay beyond 72 h was associated with even greater risks of pneumonia: OR = 2.3 (1.4–3.6, P < 0.001), prolonged LOS in HASU: OR = 1.7 (1.0–3.0, P = 0.047, median LOS = 6.2 vs. 14.7 days) and hospital: OR = 2.1-fold (1.3–3.4, P = 0.007, median LOS = 6.8 vs. 14.9 days), moderately severe to severe disability on discharge: OR = 2.5 (1.7–3.7, P < 0.001) and mortality: OR = 3.8 (2.5–5.6, P < 0.001). These risks persisted after excluding 103 patients who died within 72 h. Conclusions Delay in early screening for swallow capacity in acute stroke patients is detrimental to outcomes, possibly due to delaying nutritional provision or through inappropriate feeding leading to aspiration. Routine early screening needs greater attention in HASUs.